Environmental Variability Shapes Life‐History Trade‐Offs Within and Between Populations of a Long‐Lived Seabird - Bertille Mohring; Jonathan R. Potts; Alastair J. Wilson; Denis Réale; Richard A. Phillips; Henri Weimerskirch; Christophe Barbraud; Ashley Bennison; Karine Delord; Andrew G. Wood; Samuel Peroteau; Etienne Rouby; et al. (Ecology Letters, 2026)
Individuals face a trade‐off between allocating resources to reproduction or self‐maintenance, yet the drivers of the existence and strength of such trade‐off have been hard to determine. Environmental conditions are thought to play a crucial role, as long‐lived species are predicted to favour more precautionary life‐history strategies in variable environments. However, empirical evidence remains limited. Using long‐term monitoring of two black‐browed albatross Thalassarche melanophris populations, we investigated variation in life‐history strategies under contrasting environmental conditions, through reproductive senescence. In more variable environments, individuals displayed generally slower life histories (i.e., slow, late‐onset senescence) and greater among‐individual variation in life‐history strategies. Interestingly, earlier and faster reproductive senescence correlated with higher lifetime reproductive success regardless of environmental variability, suggesting that either faster life histories incur higher fitness or successful reproduction accelerates reproductive senescence. These findings reveal how environmental variability shapes life‐history strategies, highlighting potential responses to increasing environmental variability in a changing world.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Surface disturbances of fluid due to vertical surface-piercing cylinder - Martin Kocan; Douglas A. Potts; Jonathan R. Binns; Alexei T. Skvortsov (Wave Motion, 2025)

The potential contribution of citizen science data in the study of coastal microplastic and mesoplastic distributions - David M. Jones; Jonathan Potts; Michelle S. Hale (Environmental Monitoring and Assessment, 2025)
Plastic pollution in marine environments is an escalating global issue, particularly in coastal regions where geomorphic processes and relatively high waste input can lead to significant accumulation. In this study, we analysed citizen science (CS) data from the Big Microplastic Survey (BMS), collected by volunteers across 39 countries between March 2018 and April 2024. The BMS project provided information about microplastic (MP) and mesoplastic (MEP) distributions from coastlines around the world. Using descriptive statistics, we examined volunteer participation and engagement, as well as the geographical distribution of MPs and MEPs based on characteristics and colour. Our analysis highlighted some of the challenges associated with CS projects and the importance of organisational affiliations in influencing data submission. There was substantial variability in the geographical distributions of plastics, suggesting regional pollution dynamics that were influenced by both anthropogenic and natural coastal processes. In this study, our analysis of global, regional, and localised data underscored the value of CS in augmenting traditional scientific methods, providing critical insights into coastal plastic pollution, and potentially engaging communities in environmental stewardship. We also discovered that engaging with non-governmental organisations (NGOs) was particularly effective in facilitating data collection. We advocate for a strategic focus on organisational participation in CS projects, to improve data collection and assess spatial and temporal trends more fully.

Increasing our understanding of coastal microplastics and mesoplastics: a comparison of sampling methodologies using volunteer researchers - David M. Jones; Jonathan Potts; Michelle S. Hale (Journal of Coastal Conservation, 2025)
Coastal microplastic and mesoplastic pollution has become a significant issue for the environment, ecosystems and potentially human health, and the problem is so pervasive that traditional science is struggling to measure its true impact. Citizen science research projects in this field present an opportunity to augment existing research and potentially provide benefits to the volunteers. However, different sampling methodologies and the absence of a standardised protocol, makes it difficult to make meaningful comparisons between data collected globally. In this study we compared three existing sampling protocols. These methods included two citizen science sampling protocols, the Big Microplastic Survey (BMS), and the Australian Microplastic Assessment Project (AUSMAP), and the scientific recommendations of the European Union Marine Strategy Framework Directive (MSFD). We used volunteers to undertake the sampling in both uncoordinated and coordinated surveys across three locations in the south of the UK. In two locations we found that the BMS method consistently provided higher counts of plastic pollution, and fewer zero counts than the AUSMAP and MSFD methods. In another location, BMS and AUSMAP produced comparable results. We conclude that standardisation remains a challenge, and that further research should focus on establishing a means to allow data collected by different methods to be compared.

Journeys of change towards the blue economy: evaluating process in transformational change - Tegan Evans; Stephen Fletcher; Pierre Failler; Antaya March; Jonathan Potts (Regional Environmental Change, 2024)
Transformation is idealised as a solution to multiple ocean crises, and the blue economy has emerged as a paradigm to facilitate transformation towards a sustainable ocean future. Conceptualisations of transformation differ and processes of change to achieve transformation remain under-explored in literature, representing a significant gap in understanding how transformation is achieved. By exploring the process of blue economy governance transformations in Seychelles and Bangladesh, key attributes of transformation as a process are identified and contextualised. Connectivity of events and actions that addressed a range of different depths and parts of the governance system were identified as enablers of progress towards the blue economy. Strong, centralised leadership was identified as important at an early stage of change, but this must evolve to a distributed form of leadership to continue direction and flexibility. The role and importance of external agencies in creating and catalysing change is complex, presenting challenges to sovereignty but also acts as an independent driver of movement. From a national government perspective, the need to be ‘constantly seen as doing something’ hinders deeper changes and interventions, and instead promotes more superficial outcomes. These results demonstrate the challenges in creating transformative change, and suggest a need to explore evolutionary processes of change over time.

Using a multi-scale approach to examine the effects of field margins and landscape features on predatory carabid communities in crop fields - Kelly Jowett; Alice E. Milne; Dion Garrett; Dan Blumgart; Simon G. Potts; Deepa Senapathi; Jonathan Storkey (Agriculture, Ecosystems & Environment, 2024)

Radical and incremental, a multi-leverage point approach to transformation in ocean governance - Tegan Evans; Stephen Fletcher; Pierre Failler; Ruth Fletcher; Jonathan Potts (Sustainability Science, 2024)
Urgent change is required in the governance of ocean spaces to contend with the increasing presence and impact of human activities, the solution to which is often labelled a ‘transformation.’ While diverse interpretations of this concept exist across academic disciplines, a grounded exploration of the subject with those involved in ocean governance has not been undertaken and is a critical gap in the practical implementation of the concept. Leverage points have been not only identified as a mechanism for change, but also face similar research challenges. Therefore, this research aimed to identify, through 24 expert and practitioner interviews, what exactly transformation means in the context of ocean governance, and how it can be achieved through a leverage points approach. While reactions to and perceptions of the concept were mixed, several definitions of transformation were identified, ultimately hinging on incremental and radical change to define character. A multi-intervention ‘puzzle’ style of leverage points is advocated for. Therefore, ocean governance transformation is proposed to be achieved through a model that recognises the utility and benefits of both radical and incremental change and employs a multi-leverage approach, using interventions at varying depths across the system.

Coastal microplastic pollution: Understanding coastal community stakeholder perceptions and resolution priorities - David M. Jones; Jonathan Potts; Michelle S. Hale (Ocean & Coastal Management, 2024)

New Oldowan locality Sare-Abururu (ca. 1.7 Ma) provides evidence of diverse hominin behaviors on the Homa Peninsula, Kenya - Emma M. Finestone; Thomas W. Plummer; Thomas H. Vincent; Scott A. Blumenthal; Peter W. Ditchfield; Laura C. Bishop; James S. Oliver; Andy I.R. Herries; Christopher Vere Palfery; Timothy P. Lane; Elizabeth McGuire; Jonathan S. Reeves; et al. (Journal of Human Evolution, 2024)

The sampling and analysis of coastal microplastic and mesoplastic: Development of a citizen science approach - David M. Jones; Jonathan Potts; Michelle S. Hale (Journal of Coastal Conservation, 2024)
Plastic pollution has become one of the major environmental issues affecting the oceans. Millions of tonnes of plastic pollution enter the oceans every year and much of that ends up on coastlines. Microplastics and mesoplastics contamination is of particular concern, however, despite increased research, much remains unknown about their scale, distribution and impacts around the world. This study sought to determine whether a citizen science approach to coastal microplastic and mesoplastic data collection could address some of these shortcomings. We designed, developed, and tested a novel protocol that would allow volunteers to collect and record reliable data. Using the final protocol, a total of 910 samples have been collected by volunteers from 32 countries over the period of the research. This study showed that by incorporating user-centred design with established scientific methods and adapting the protocol design through user feedback, volunteers can collect data, make meaningful contributions to the gaps in scientific knowledge, benefit personally and increase their understanding of the impacts of microplastics in the environment.

Untangling theories of transformation: Reflections for ocean governance - Tegan Evans; Stephen Fletcher; Pierre Failler; Jonathan Potts (Marine Policy, 2023)

Belize Blue Carbon: Establishing a national carbon stock estimate for mangrove ecosystems - Hannah K. Morrissette; Stacy K. Baez; Lisa Beers; Nadia Bood; Ninon D. Martinez; Kevin Novelo; Gilbert Andrews; Luis Balan; C. Scott Beers; Sumeet A. Betancourt; Reynel Blanco; Eeryn Bowden; et al. (Science of The Total Environment, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Effects of dolphin-swim activities on the behaviour of an Indo-Pacific bottlenose dolphin population off the south coast of Mozambique - Diana Rocha; Sarah A. Marley; Benjamin Drakeford; Jonathan Potts; Angie Gullan (Biological Conservation, 2023)

The benefits of guide training for sustainable cetacean-based tourism in developing countries, case study – Ponta do Ouro Partial Marine Reserve, Mozambique - Diana Rocha; Sarah A. Marley; Benjamin Drakeford; Jonathan Potts; Angie Gullan (Journal of Coastal Conservation, 2022)
Tour guides represent the forefront of responsible Cetacean-Based Tourism (CBT), client satisfaction and product development. How an operation and specifically the guide facilitates the activity can shape tourists’ attitudes and change their behaviour towards the environment, turning consumers into stewards of the environment. This study examined the validity and success of a guide training workshop for CBT operators in the Ponta do Ouro Partial Marine Reserve (PPMR), Mozambique. A questionnaire survey was implemented pre- and post-training to measure the operators’ knowledge of aspects related to CBT and attitudes towards sustainable tourism and local regulations. Results suggest that the training workshop improved guide knowledge, which in some cases showed significant variations according to demographic variables namely, gender, education, and years of experience in the current job position. Mandatory guide training is recommended and should include not only product knowledge but also content on visitors’ expectations, interpretive guiding, and experience brokering. Presential training, refresher sessions, and English lessons are also advised. If these recommendations are put in place, then there is the potential for sustainable CBT to flourish in Mozambique, bringing much needed environmental and economic sustainability to this developing country.

Differences in the temporal scale of reproductive investment across the slow‐fast continuum in a passerine - Samantha C. Patrick; Denis Réale; Jonathan R. Potts; Alastair J. Wilson; Claire Doutrelant; Céline Teplitsky; Anne Charmantier (Ecology Letters, 2022)
Life‐history strategies differ with respect to investment in current versus ‘future’ reproduction, but when is this future? Under the novel ‘temporality in reproductive investment hypothesis’, we postulate variation should exist in the time frame over which reproductive costs are paid. Slow‐paced individuals should pay reproductive costs over short (e.g. inter‐annual) time scales to prevent reproductive costs accumulating, whereas fast‐paced individuals should allow costs to accumulate (i.e. senescence). Using Fourier transforms, we quantify adjustments in clutch size with age, across four populations of blue tits ( Cyanistes caeruleus ). Fast populations had more prevalent and stronger long‐term changes in reproductive investment, whereas slower populations had more prevalent short‐term adjustments. Inter‐annual environmental variation partly accounted for short‐, but not long‐term changes in reproductive investment. Our study reveals individuals differ in when they pay the cost of reproduction and that failure to partition this variation across different temporal scales and environments could underestimate reproductive trade‐offs.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Be different to be better: the effect of personality on optimal foraging with incomplete knowledge - Poppy M. Jeffries; Samantha C. Patrick; Jonathan R. Potts (Theoretical Ecology, 2021)
Many animal populations include a diversity of personalities, and these personalities are often linked to foraging strategy. However, it is not always clear why populations should evolve to have this diversity. Indeed, optimal foraging theory typically seeks out a single optimal strategy for individuals in a population. So why do we, in fact, see a variety of strategies existing in a single population? Here, we aim to provide insight into this conundrum by modelling the particular case of foraging seabirds, that forage on patchy prey. These seabirds have only partial knowledge of their environment: they do not know exactly where the next patch will emerge, but they may have some understanding of which locations are more likely to lead to patch emergence than others. Many existing optimal foraging studies assume either complete knowledge (e.g. Marginal Value Theorem) or no knowledge (e.g. Lévy Flight Hypothesis), but here we construct a new modelling approach which incorporates partial knowledge. In our model, different foraging strategies are favoured by different birds along the bold-shy personality continuum, so we can assess the optimality of a personality type. We show that it is optimal to be shy (resp. bold) when living in a population of bold (resp. shy) birds. This observation gives a plausible mechanism behind the emergence of diverse personalities. We also show that environmental degradation is likely to favour shyer birds and cause a decrease in diversity of personality over time.

Deciding when to intrude on a neighbour: quantifying behavioural mechanisms for temporary territory expansion - Jonathan R. Potts; William F. Fagan; Guilherme Mourão (Theoretical Ecology, 2019)

The “edge effect” phenomenon: deriving population abundance patterns from individual animal movement decisions - Jonathan R. Potts; Thomas Hillen; Mark A. Lewis (Theoretical Ecology, 2016)

Variation in plant diversity in mediterranean‐climate ecosystems: the role of climatic and topographical stability - Richard M. Cowling; Alastair J. Potts; Peter L. Bradshaw; Jonathan Colville; Margarita Arianoutsou; Simon Ferrier; Felix Forest; Nikolaos M. Fyllas; Stephen D. Hopper; Fernando Ojeda; Şerban Procheş; Rhian J. Smith; et al. (Journal of Biogeography, 2015)
Aim Although all five of the major mediterranean‐climate ecosystems ( MCE s) of the world are recognized as loci of high plant species diversity and endemism, they show considerable variation in regional‐scale richness. Here, we assess the role of stable Pleistocene climate and Cenozoic topography in explaining variation in regional richness of the globe's MCE s. We hypothesize that older, more climatically stable MCE s would support more species, because they have had more time for species to accumulate than MCE s that were historically subject to greater topographic upheavals and fluctuating climates. Location South‐western Africa (Cape), south‐western Australia, California, central Chile and the eastern (Greece) and western (Spain) Mediterranean Basin. Methods We estimated plant diversity for each MCE as the intercepts of species–area curves that are homogeneous in slope across all regions. We used two down‐scaled global circulation models of the Last Glacial Maximum ( LGM ) to quantify climate stability by comparing the change in the location of MCE s between the LGM and present. We quantified the Cenozoic topographic stability of each MCE by comparing contemporary topographic profiles with those present in the late Oligocene and the early Pliocene. Results The most diverse MCE s – Cape and Australia – had the highest Cenozoic environmental stability, and the least diverse – Chile and California – had the lowest stability. Main conclusions Variation in plant diversity in MCE s is likely to be a consequence not of differences in diversification rates, but rather the persistence of numerous pre‐Pliocene clades in the more stable MCE s. The extraordinary plant diversity of the Cape is a consequence of the combined effects of both mature and recent radiations, the latter associated with increased habitat heterogeneity produced by mild tectonic uplift in the Neogene.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Towards an assessment of multiple ecosystem processes and services via functional traits - Francesco de Bello; Sandra Lavorel; Sandra Díaz; Richard Harrington; Johannes H. C. Cornelissen; Richard D. Bardgett; Matty P. Berg; Pablo Cipriotti; Christian K. Feld; Daniel Hering; Pedro Martins da Silva; Simon G. Potts; et al. (Biodiversity and Conservation, 2010)

Stability of Genetic-Based Defensive Chemistry Across Life Stages in a Eucalyptus Species - Julianne M. O’Reilly-Wapstra; Jonathan R. Humphreys; Brad M. Potts (Journal of Chemical Ecology, 2007)